Desarrollo e implementación de un sistema de seguimiento y control de proyectos de tesis e investigación para la Universidad Técnica de Machala - Tinoco Miranda, Jefferson Efraín (2014)
After study at the Technical University of Machala, prior to the development of this project graduation, it is evident from the outset that each of the faculties of the University have managed titling procedures and research projects manually, with the Over the years they have taken the initiative to automate some processes through individual and independent computer systems in order to take proper management, however titling processes and research projects have not been automated.